2013
DOI: 10.1111/febs.12534
|View full text |Cite
|
Sign up to set email alerts
|

Insights into subunit interactions in the Sulfolobus acidocaldarius archaellum cytoplasmic complex

Abstract: Archaella are the archaeal motility structure that is the functional pendant of the bacterial flagellum but is assembled by a mechanism similar to that for type IV pili. Recently, it was shown by Banerjee et al. that FlaX, a crenarchaeal archaellum subunit from Sulfolobus acidocaldarius, forms a ringlike oligomer, and it was proposed that this ring may act as a static platform for torque generation in archaellum rotation [Banerjee A et al. (2012) J Biol Chem 287, 43322-43330]. Moreover, the hexameric crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 24 publications
0
59
0
Order By: Relevance
“…The same considerations apply to branch A3, which includes KaiC-like proteins with two active ATPase domains. The third branch (A17) that appears to be ancestral consists of FlaH proteins, essential archaellum components (36,45). The remaining tree branches are either lineage specific or include only a few archaeal lineages ( Table 2; Table S3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same considerations apply to branch A3, which includes KaiC-like proteins with two active ATPase domains. The third branch (A17) that appears to be ancestral consists of FlaH proteins, essential archaellum components (36,45). The remaining tree branches are either lineage specific or include only a few archaeal lineages ( Table 2; Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…The multiple lines of evidence discussed above indicate that the KaiC family is likely a major hub of a versatile and complex archaeal signaling network that so far has largely escaped attention. Nevertheless, the available experimental data on a halobacterial circadian clock (24,57) and the recent progress in the study of the functions of FlaH in the archaellum (35,36,45) allow us to propose two models of the roles of KaiC-like proteins in signal transduction (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…That is in contrast to the anchoring structure supposed for bacterial type IV pili, which is assumed to be located in or directly underneath the inner membrane (56); however, a definite localization of this structure is absent. In addition, hardly any information is reported concerning the anchoring structure of archaeal flagella, with the notable exception of Sulfolobus: here, some biochemical data exist (57). Direct structural data obtained by electron microscopy are poor or missing, however.…”
Section: Discussionmentioning
confidence: 99%
“…Formation of "rods" of the cytoplasmic domain of GspL were recently observed in several crystal structures (68), suggesting that similar to GspL a higher oligomeric form of PilM is assembled in the presence of nucleotides and may play a role in the assembly or the function of the T4P system. In archaea, this role might be fulfilled by either the FlaH ATPase that interacts with the FlaI secretion ATPase (69) or FlaX (38), a membrane protein with a cytosolic domain that forms a ring-like structure around the FlaI secretion ATPase. Importantly, in our pulldown and co-purification experiments, we observed that PilM and hexameric PilB interact directly, whereas an interaction was neither observed between PilM and solubilized PilC nor between PilM and PilC in proteoliposomes.…”
Section: Discussionmentioning
confidence: 99%